Time resolved electron density and temperature measurements via Thomson scattering in an atmospheric nanosecond pulsed discharge. (28th July 2020) - Miles, Jared; Murray, Chase; Ross, Ajani; Lemmer, Kristina; Russell, Jacob; Adams, Steven
Abstract: This work details electron density and temperature measurements within an atmospheric nanosecond repetitively pulsed discharge in air using Thomson scattering. High voltage pulses up to 15 kV were applied to a pin-to-pin electrode configuration at several repetition frequencies to determine the effect of successive pulses on the electron parameters. Electron densities on the order of 10 17  cm −3 are measured within hundreds of nanoseconds after the discharge, with densities of 10 14  cm −3 still present in the region up to 20 μ s after the initial pulse discharge. Subsequent high voltage pulses reignite the plasma, increasing the electron density from the previous pulse if the repetition frequency is above a critical value. Electron temperatures and densities were recorded at various times after the initial pulse and between subsequent pulses.